Vacancy influence on the stabilization of martensitic Cu–Zn–Al single crystals - Stipcich, Marcelo Fernando (2006)
On a well-ordered beta phase Cu–Zn–Al single crystal, the vacancy influence on martensitic stabilization has been studied by compression tests. Systematic studies on the influence of stabilization time, temperature, and the influence of the vacancy concentration on the stabilization process show that the characteristic time for stabilization and vacancy migration are several orders of magnitude different. It is found that only a small fraction of the initial vacancy concentration contributes to the process and that the remnant vacancies are unable to promote further stabilization.A model is proposed witch can reproduce the essential features of isothermal martensite stabilization.